2022
DOI: 10.1177/17531934221101998
|View full text |Cite
|
Sign up to set email alerts
|

Abductor pollicis brevis rerouting and first web deepening for clasped thumb deformity in arthrogryposis multiplex congenita

Abstract: In this study, we retrospectively reviewed our results of managing the clasped thumb deformity in arthrogryposis multiplex congenita patients with first web space deepening and abductor pollicis brevis (APB) rerouting. Twenty-six thumb deformities in 16 children with a mean age of 6.2 years were treated with a mean follow-up of 89.6 months. Following reconstruction with the Spinner flap, the mean angle of the first and second metacarpal axis (M1M2) showed significant improvement from 42° to 61° indicating a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Anbarasan et al (10) reported the results of abductor pollicis brevis rerouting in congenital clasped thumb in arthrogryposis multiplex congenita. They used a polystyrene cone for radiographic assessment of the first web space (9) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anbarasan et al (10) reported the results of abductor pollicis brevis rerouting in congenital clasped thumb in arthrogryposis multiplex congenita. They used a polystyrene cone for radiographic assessment of the first web space (9) .…”
Section: Resultsmentioning
confidence: 99%
“…They reported that the rerouted tendon acts as a static tenodesis of the MCP joint in extended position. However, they had 2 cases of MCP instability that required revision by chondrodesis (10) .…”
Section: Resultsmentioning
confidence: 99%
“…The total active movement (TAM) of metacarpophalangeal joints (MPJ) and PIPJ and the extensor lag of PIPJ of the affected fingers were recorded using a goniometer to evaluate camptodactyly. The thumb-to-index finger metacarpal angle (M1M2 angle) and the degree of deviation at the first MPJ (M1P1 angle) were measured with the first web space open to assess the clasped thumb ( 13 ). The PedsQL 4.0 Generic Core Scales were used to assess the quality of life patients.…”
Section: Methodsmentioning
confidence: 99%